1981
DOI: 10.5014/ajot.35.11.705
|View full text |Cite
|
Sign up to set email alerts
|

Handedness and Hand Joint Changes in Rheumatoid Arthritis

Abstract: This study investigates the relationship of hand use to the deforming hand joint changes of rheumatoid arthritis. Measurements of metacarpophalangeal lateral mobility, loss of metacarpophalangeal hyperextension, thumb metacarpophalangeal range of motion, and lateral pinch strength were statistically compared across dominant and nondominant hands of 51 adult subjects who had definite or classical rheumatoid arthritis. Incidence of boutonniere and swan neck deformities and distal radioulna laxity was also record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…Instead, they found no significant difference in the incidence of rheumatoid deformities between the hands. 35 Mody et al 36 confirmed the result.…”
Section: Avoid Deforming Positionssupporting
confidence: 81%
“…Instead, they found no significant difference in the incidence of rheumatoid deformities between the hands. 35 Mody et al 36 confirmed the result.…”
Section: Avoid Deforming Positionssupporting
confidence: 81%
“…We chose six reports141516172021 and an additional three reports referred to in the six reports (for detail, see Materials and Methods)181922. Thus, a total of nine previous reports were identified (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The hit number was 52. We chose six reports that included “handedness” or “dominant hand” in the title141617202130. The other 46 reports were excluded from the following analyses since they were not directly about the association between handedness and symptoms or outcomes in RA.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, from my own research study on day-care staff satisfactions and dissatisfactions in caring for persons with dementia, I have, thus far, published three papers (each in a different journal). In one paper, I focused on the everyday ethical dilemmas in the data (Hasselkus, 1997); in the second paper, I focused on the uncertain endings of day care described in the data (Hasselkus & LaBelle, 1998); and in the third paper, I focused on the nature of occupation in the data (Hasselkus, 1998). Each paper required its own (though overlapping) literature review, its own analysis of the data, and its own generation of findings and disdiscussion.…”
mentioning
confidence: 99%